ISOLATION AND INTRODUCTION INTO CULTURE OF A NEW STRAIN OF CHLAMYDOMONAS PARIENTARIA. DILL (World Bulletin of Management and Law, 2023)
In the article, the dominant species of algoflora in the bioponds of the Namangan city sewage treatment plant were isolated in an algologically pure state. Information on the introduction of a new species of Parietaria into culture. Data on photosynthetic productivity and morphology are presented